The chronic damage in systemic lupus erythematosus is driven by flares, glucocorticoids and antiphospholipid antibodies: results from a monocentric cohort. (June 2016) - Conti, F; Ceccarelli, F; Perricone, C; Leccese, I; Massaro, L; Pacucci, V A; Truglia, S; Miranda, F; Spinelli, F R; Alessandri, C; Valesini, G
Objectives: Literature data suggest a significantly higher mortality in patients affected by systemic lupus erythematosus (SLE) developing chronic damage. Therefore, damage prevention is a major goal in the management of SLE patients. In the present study, we assessed damage by means of the Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) damage index (SDI), in a large cohort of SLE patients. Additionally, we aimed at evaluating its association with demographic and clinical features as well as with disease activity and laboratory findings. Patients and methods: We enrolled consecutive patients affected by SLE diagnosed according to the American College of Rheumatology (ACR) 1997 revised criteria. Chronic damage was determined by SDI calculated at the last examination in all patients with at least six months of follow-up. Disease activity was assessed by the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K); flare was defined as an increase of SLEDAI-2K ≥ 4 compared with the previous visit. Results: We evaluated 349 SLE patients (M/F 25/324, mean age ± SD 42.7 ± 12.4 years, mean disease duration ± SD 164.9 ± 105.2 months). Among the enrolled patients, 125 (35.8%) showed a SDI ≥ 1 (mean SDI ± SD 1.7 ± 0.9, range 0–5). The musculo-skeletal was the most frequently involved organ/system in SDI score (41/349 patients, 11.7%), with deforming/erosive arthritis in 21/349 (6.0%). The presence of chronic damage was associated with age ( P < 0.001), disease duration ( P < 0.001), number of flares ( P = 0.02) and with the use of glucocorticoids ( P = 0.02). The logistic regression analysis revealed the association between neuropsychiatric damage and antiphospholipid syndrome ( P = 0.01, OR = 3.9) and between the presence of cardiovascular damage and anti-β2GPI antibodies ( P = 0.01, OR 6.2). Conclusions: In the present study chronic damage was identified in about one third of SLE patients. The association between SDI and the number of flares claim for a thigh-control of the disease activity in order to prevent the chronic damage. The possible role of antiphospholipid antibodies (aPL) in the development of neuropsychiatric and cardiovascular damage may suggest a more careful assessment of such aPL positive patients.